#TITLE_ALTERNATIVE# - INDRIANI (NIM: 22209068), ERDILA
In this study, the Genetic Algorithm is intended to obtain optimum horizontal drilling length and direction. The length and the direction would affect economic parameters such as Net Present Value and Internal Rate of Return because they are directly related to cumulative gas productions as resulted from running process of the X field reservoir simulation, and thus, each drilling direction and length has different NPV and IRR. The results of the reservoir simulation are used to validate the results of the Genetic Algorithm calculation for various percentage numbers of a total data as used by the reservoir simulation. Based on this result, it was obtained a conclusion that the length of horizontal segment of 669 meters at 3150 drilling direction yields the highest NPV, i.e., $183,804,215.